Differences in body mass index and height factors between men with and without varicocele - Hamid Shafi; Mouloud Agajani Delavar (Medicinski glasnik, 2015)
Aim: Despite many studies published in recent years concerning the relationship between demographic factors and varicocele, this issue remains controversial. The aim of this study was to identify a possible influence of body mass index (BMI) and height on occurrence varicocele in men. Methods: In a case-control study 153 patients aged 18-40 years from 2004 to 20014, with moderate and sever varicocele were studied. The BMI and height of the 153 patients with varicocele were compared with 250 men who had no varicocele as a control group. Results: After the adjustment for socio-demographic factors, the risk of varicocele for obese men was lower than for overweight and normal men (OR= 0.38, 95% CI= 0.17, 0.85). The adjusted OR for varicocele in taller men was higher than in those with low height (OR= 3.42, 95% CI= 1.34, 8.72), and moderate height (OR=2.68, 95% CI= 1.12, 6.46). Conclusion: The results of this study indicated that tall men and non-obese men may be at higher risk of varicocele, therefore counseling and evaluation of the men at high risk of varicocele may be of benefit for reduced infertility.
Keywords: pampiniform plexus; spermatic vein; anthropometric parameters